Single Euro Payments Area (SEPA) – Strategic Value on the High Degree of Interoperability for All Active Participants in the Financial Transaction Market (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The introduction of euro currency in 1999 paved the way for policymakers - EU governments, the European Parliament, the European Commission and the European Central Bank - to adopt the SEPA initiative. This is a complex process that aims to integrate the euro payments market, integration that also takes into account Romanian State Treasuries as payment service providers for local and central public administrations. In this context, premises were created for developing an integrated financial market that would allow a better use of capital and an accelerating economic development in the EU.